2014
DOI: 10.1021/je400938a
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Stability Study of Sodium Cefuroxime

Abstract: The stability of sodium cefuroxime has been a major concern since it was invented as a valuable antibiotic. In this study, online attenuated total reflection-fourier transform infrared spectroscopy was applied to monitor the change in supersaturation and optimize the solvent flow rate in antisolvent recrystallization experiments of sodium cefuroxime. The solubility of sodium cefuroxime under various temperatures T, pH values, and solvents was measured and correlated in models. The effect of the antisolvent (79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Furthermore, comparing with the stability test (3, 5, 7, and 10 days), XRD spectra can be measured quickly and gives direct evidence of the process optimization. Three sharp peaks of the XRD spectra of sodium cefuroxime were observed at 2 θ values of 9°–10.5°, 10.5°–13°, and 14°–15° . The peak intensity and peak width at half height of peak between 9° and 10.5° were chosen to present the crystallinity of sodium cefuroxime for quantification in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, comparing with the stability test (3, 5, 7, and 10 days), XRD spectra can be measured quickly and gives direct evidence of the process optimization. Three sharp peaks of the XRD spectra of sodium cefuroxime were observed at 2 θ values of 9°–10.5°, 10.5°–13°, and 14°–15° . The peak intensity and peak width at half height of peak between 9° and 10.5° were chosen to present the crystallinity of sodium cefuroxime for quantification in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In the storage and transportation processes, it tends to deepen solid color, reduce solubility, and become sticky . In our previous paper, cefuroxime sodium has only one polymorphic form and exists as a mixture of crystal and amorphous state. The general view is that the stability of drugs in the amorphous form is usually lower than the crystalline form, because of the higher free energy level under the amorphous form.…”
Section: Materials and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found that sodium cefuroxime is insoluble in acetone [8]. However, there was research focused on neither the influence of pH value on solubility of sodium cefuroxime nor provided any data.…”
Section: Solubility Of Sodium Cefuroximementioning
confidence: 99%